Mitochondrial Genome Analysis of Babesia ovis (Apicomplexa: Babesiidae) Endemic in Sheep in Türkiye - Ulucesme, Mehmet Can; Aktas, Munir; Ozubek, Sezayi (Mdpi, 2024)
This study presents the first comprehensive analysis of the mitochondrial genome of Babesia ovis, a significant pathogen in ovine babesiosis in T & uuml;rkiye. The B. ovis mitochondrial genome is a linear monomeric molecule of 6015 bp with an A + T content of 70.5%, featuring terminal inverted repeats (TIRs) at both ends. It encodes three essential proteins (Cox1, Cox3, and Cob) and six fragments of large subunit rRNA genes. Comparative analysis revealed high sequence identity with Babesia sp. Xinjiang (87.5%) and Babesia sp. Dunhuang (87.5%), suggesting a close evolutionary relationship. The study highlights the conservation of mitochondrial gene content across Babesia and Theileria species, emphasizing their utility in phylogenetic studies. The findings also suggest that TIR variability plays a role in mitochondrial genome size differences, influencing species-specific adaptations. This research provides valuable insights into the evolution and functional adaptations of B. ovis and underscores the potential of mitochondrial genomic data in enhancing diagnostic and therapeutic strategies for babesiosis. Further exploration of mitochondrial genomes in Babesia species is essential for understanding their biology and developing effective control measures.
Keywords: Babesia ovis; mitochondrial genome; phylogenetic; evolutionary biology; ovine babesiosis